A reflexividade nos discursos identitários da capoeira - Almeida, Juliana Azevedo de (2008)
The research identifies how the “capoeira” identitary narratives are structured and legitimated, having as basis the reflexive modernity. The reflexive process takes place through the information between the different fields of knowledge production about a determined social practice that is always under reformulation (GIDDENS, 2002). This way, the study verifies how the “capoeira” discourse interpretation produced by practitioners and academics in the speeches of the daily life and texts is made. First of all, it maps and analyses the discourses about the “capoeira” linked to the magazine “Revista Brasileira de Ciências do Esporte” (RBCE), concluding that the same brings, between the lines, the conservator and nationalist tone that intends to rescue/preserve ethno cultural “capoeira” trace. After, it identifies and interprets the elements and ways of identitary affirmation produced in a “capoeira” group, tracing a parallel with the academic discourses analyzed. The work has as methodological tool the ethnography and uses the participant observation and semi structured interviews as instruments for data collection. It proves the existence of reflexivity among the discourses of the fields mentioned; however, it calls attention for the articulation with other systems of information production and for the factors of the reflexive process that filters the knowledge and promotes the specificities of each “capoeira” group and each society. Besides, it points the relations between the representations of the practical environment and the reality of the Brazilian society, highlighting that the practitioners discourse is more innovator than the academic one. Although, in essence, both discourses are similar, because they value cultural elements (re)affirming the Brazilian way and reproduce values of a country marked by traditionalism. Such tendency of discourses, besides searching for standing out the “value” of “capoeira” in the markets, it also represents a way to make stronger the links with the nation in the midst of risks and uncertainness of the modernity. It concludes that, in “capoeira”, the reflexivity is manifested in an incomplete way, what represents the actual reality of a country that is in process of modernization and, consequently, of reappearing of the national